Robust predictive control for anti-rolling path following of underactuated surface vessels using adaptive Kalman filter. (24th September 2019) - Li, Guosheng; Liu, Zhilin; Zhang, Jun; Zheng, Linhe
With the strong time-varying disturbances in wave fields, the large sway motion of underactuated surface vessels can be caused leading to the control performance reduction and large range of roll angle, such that a novel path following control with roll constraints is proposed. Firstly, the affine switching system model is constructed with coupled surge, sway, roll, and yaw. Then, with augmented state adaptive Kalman filter, the estimations of system state and disturbance can be obtained for the feedforward compensation. Considering the existing estimation error between real and estimated states, the state estimation has been adopted directly in the controller design for the performance improvements. With the convex optimization of linear matrix inequalities, the invariant ellipsoid constraint ensures the close-loop system uniformly bounded and stable. Lastly, the simulation results have verified the effectiveness of the designed control approach.